2017
DOI: 10.2174/1570159x14666161026151545
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Beyond Barriers: A Glimpse into the Brain

Abstract: BackgroundAgeing can be simply defined as the process of becoming older, which is genetically determined but also environmentally modulated. With the continuous increase of life expectancy, quality of life during ageing has become one of the biggest challenges of developed countries. The quest for a healthy ageing has led to the extensive study of plant polyphenols with the aim to prevent age-associated deterioration and diseases, including neurodegenerative diseases. The world of polyphenols has fascinated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 346 publications
(329 reference statements)
1
97
0
Order By: Relevance
“…In addition to the used polyphenol dose, the bioavailability of the ingested phenolic compounds is usually reported as an important factor influencing the change on cognition and brain function [57,58]. From a pharmacological perspective, bioavailability is the rate and extent to which the bioactive compound is absorbed and becomes available at the site of action [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the used polyphenol dose, the bioavailability of the ingested phenolic compounds is usually reported as an important factor influencing the change on cognition and brain function [57,58]. From a pharmacological perspective, bioavailability is the rate and extent to which the bioactive compound is absorbed and becomes available at the site of action [59].…”
Section: Discussionmentioning
confidence: 99%
“…From a pharmacological perspective, bioavailability is the rate and extent to which the bioactive compound is absorbed and becomes available at the site of action [59]. In other words, this rate reflects the ability of the bioactive compound to cross membranes/barriers and to reach the tissues in an appropriate amount of time to exert its effect [57,60]. Variation in phenolic bioavailability ranges from 0.3% to 43% [21], with isoflavones (≈43%) and Gallic acid (≈38%) representing the most well-absorbed polyphenols, followed by catechins (≈18%), flavanones (≈9%), and quercetin glucosides (≈2.5%); the least well-absorbed polyphenols (<1%) are the proanthocyanidins, the galloylated tea catechins, and the anthocyanins [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective efficacy of quercetin has been studied in both in vitro and in vivo models [50,110,111]. A study using drug screening in Caenorhabditis elegans nematodes with neuronal expression of human exon-1 huntingtin (128Q) and mutant Htt striatal cells derived from knock-in HD mice, concluded that isoquercetin improved motor functions in acute spinal cord injury, reduced α-synuclein fibrillization, reduced hippocampal neuronal cell death, improved synaptic plasticity, and reversed histopathological hallmarks of AD [112]. Quercetin also protects against mitochondrial dysfunction and progressive dopaminergic neurodegeneration by activating PKD1-Akt cell survival signaling axis Cell Culture and MitoPark transgenic mouse models of Parkinson's disease [113].…”
Section: Neuroprotective Efficacy Of Quercetinmentioning
confidence: 99%
“…Polyphenol content and composition can vary substantially between fleshyfruit varieties Miladinović et al 2014;Kula et al 2016), different cultivation conditions (Josuttis et al 2013;Vagiri et al 2013;Mazur et al 2014), harvest times and as a result of different post-harvest factors (Kårlund et al 2014;Stavang et al 2015), but particularly between species (Moyer et al 2001;McDougall et al 2008;Ruiz et al 2010;Marhuenda et al 2016). Furthermore, plant polyphenols are increasingly being associated with putative bioactivities offering protection against several cardiovascular (Goszcz et al 2015) and neurological diseases (Figueira et al 2017). The hydroxystilbenes are a group of polyphenols with a C 6 -C 2 -C 6 skeleton with two or more hydroxyl groups, where a central carbon-carbon double bond is conjugated with two phenolic moieties (Quideau et al 2011;Kasiotis et al 2013).…”
Section: Polyphenols As a Source Of Bioactive Moleculesmentioning
confidence: 99%
“…b PCA plots of the full dataset without reference material and blanks in negative mode. Components (Scr) 1 and 2 explain 13.20 and 10.30% of the variation respectively (Figueira et al 2017;Goszcz et al 2015 (Figueira et al 2017). Consequently, polyphenol-based therapies represent an underexplored strategy to minimize the huge social and economic impact of NDs.…”
Section: Berry Extract Bioactivity Screeningmentioning
confidence: 99%